The biosynthesis of the cannabinoids - M. Nazir Tahir; Fred Shahbazi; Simon Rondeau-Gagné; John F. Trant (BMC, 2021)
Abstract Cannabis has been integral to Eurasian civilization for millennia, but a century of prohibition has limited investigation. With spreading legalization, science is pivoting to study the pharmacopeia of the cannabinoids, and a thorough understanding of their biosynthesis is required to engineer strains with specific cannabinoid profiles. This review surveys the biosynthesis and biochemistry of cannabinoids. The pathways and the enzymes' mechanisms of action are discussed as is the non-enzymatic decarboxylation of the cannabinoic acids. There are still many gaps in our knowledge about the biosynthesis of the cannabinoids, especially for the minor components, and this review highlights the tools and approaches that will be applied to generate an improved understanding and consequent access to these potentially biomedically-relevant materials. Graphical abstract